HUBUNGAN KEKUATAN OTOT LENGAN BAHU DAN KELENTUKAN OTOT PUNGGUNG DENGAN HASIL LEMPAR CAKRAM PADA MAHASISWA PUTRA PENJASKESREK LOKAL A ANGKATAN 2013 UNIVERSITAS RIAU - Apri Marda Marda; Saripin '; Kristi Agust Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this research was found when the writer does an observation in the field. The writer found several weaknesses in throwing, those are less of shoulder arm strength and back muscle flexibility in discus throw, wich make the result was less than maximum. The aim of this research is to know the correlation between the shoulder arm strength and the back musce flexibility toward the result of discus throwing of the male fourth semester students Class A off Physical Education of Riau University. The sample in this study was comprehensive, or involved the whole research population. Sampling technique that the write used was “total sampling” technique. To obtain the research data, the writer used expanding dynamometer for the shoulder arm strength test, Sit and Rich for the back muscle flexibility test, and throwing for the discus throwing test. The data obtained was analyzed by using a sample moment product correlation. Based on the data analysis, correlation toward Y was obtained =0,576>=0,404 and toward Y was obtained =0,602>=0,404, while dan toward Y was obtained =0,672>=0,404. It means that was accepted while was rejected, because the cerrelation on the data analysis was significant. The correaltion of a variable to another variable is determined from >.  Keywords : Shoulder Arm Muscle Strength, Back Muscle Flexibility, Discus Throw